2022
DOI: 10.2196/31889
|View full text |Cite
|
Sign up to set email alerts
|

Social Media–Based Interventions for Health Behavior Change in Low- and Middle-Income Countries: Systematic Review

Abstract: Background Despite the wealth of evidence regarding effective health behavior change techniques using digital interventions to focus on residents of high-income countries, there is limited information of a similar nature for low- and middle-income countries. Objective The aim of this review is to identify and describe the available literature on effective social media–based behavior change interventions within low- and middle-income countries. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…However, some studies have reported that their social media efforts were effective without clearly reporting quantitative data (e.g., clicks, shares, views, etc.) on social media use [ 1 ]. Future research should examine the characteristics of engagement exposure to evaluate dose-response effects—i.e., to determine whether more exposure or exposure of a specific type is associated with successful behavior change.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, some studies have reported that their social media efforts were effective without clearly reporting quantitative data (e.g., clicks, shares, views, etc.) on social media use [ 1 ]. Future research should examine the characteristics of engagement exposure to evaluate dose-response effects—i.e., to determine whether more exposure or exposure of a specific type is associated with successful behavior change.…”
Section: Discussionmentioning
confidence: 99%
“…Digital media (i.e., electronic media where data are stored in digital form) are omnipresent in modern life, but the science of how digital media impact behavior is still in its infancy [ 1 ]. For example, approximately 45% of the world’s population or 3.5 billion people use social media, with the average user spending approximately 3 h of their day overall on social media [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Digital media is central to and an integral part of modern life; however, the study of its effects on health behavior is just beginning [1]. As reported by the World Bank, 45% of the world's population or 3.5 billion people use social media.…”
Section: Introductionmentioning
confidence: 99%
“…Abad et al [4] conducted a scoping review on digital public health surveillance and revealed that only 0.8% of the related studies between 2005 and 2020 deployed a digital health surveillance system that can be used for monitoring and targeted interventions, despite its impact on the study methodology and public health actions. A recent systematic review by Seiler et al [1] found relatively few rigorous studies on the effectiveness of digital media-related behavior change campaigns and interventions. This review also found that the reporting of design, measures, data collection, and other methods needs to be improved and systematized.…”
Section: Introductionmentioning
confidence: 99%